1978
DOI: 10.1063/1.1135533
|View full text |Cite
|
Sign up to set email alerts
|

Pulse mode saturation properties of photomultiplier tubes

Abstract: The response of an RCA-4522 photomultiplier tube (35ET bialkali photocathode, 14 dynode stages) in the saturation region has been studied as a function of ambient background light intensity, photocathode illumination area, magnetic field orientation, and ambient temperature. These studies were made using various high-speed pulsed light sources. It is found that the phototube's response does vary with some of these parameters (in particular, photocathode temperature effects). However, its response is reproducib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

1979
1979
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 1 publication
0
11
0
Order By: Relevance
“…Additionally, it has been reported that temperature may have a strong effect on the PMT signal especially in non-linear regime [57]. The behavior of the PMT used in the PM VERSS was characterized by measuring LiDAR returns from a hard target in the laboratory for different CVs (i.e., gains) and a set of calibrated neutral density optical filters.…”
Section: Linearity and Dynamic Range Limitations Of The Detectormentioning
confidence: 99%
“…Additionally, it has been reported that temperature may have a strong effect on the PMT signal especially in non-linear regime [57]. The behavior of the PMT used in the PM VERSS was characterized by measuring LiDAR returns from a hard target in the laboratory for different CVs (i.e., gains) and a set of calibrated neutral density optical filters.…”
Section: Linearity and Dynamic Range Limitations Of The Detectormentioning
confidence: 99%
“…Also the area of saturation in the upper right corner retreated to some extent, which is likely to be caused by shorter decays limiting the space charge build-up time at the end of the dynode chain. [16][17][18] The lifetime gradient for low light intensities (present in Figure 8) has vanished and some elements at low gains and intensities remained empty due to signal-to-noise (S/N) issues at shorter decays.…”
Section: Resultsmentioning
confidence: 99%
“…The major sources of error while performing the measurement using a PMT are the (i) saturation effect, (ii) the presence of an after pulse, and (iii) dark current. A very large optical intensity makes the PMT response nonlinear due to the saturation effect [10][11][12]. A high intensity optical pulse PMT also exhibits an after pulse [13,14], where some amount of anode current remains for a longer time (~few µs).…”
Section: Visar and Its Signal Recording Systemmentioning
confidence: 99%